2018
DOI: 10.1007/s10295-018-2068-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of butanol production in Clostridium acetobutylicum through enhancement of NAD(P)H availability

Abstract: Clostridium acetobutylicum is a natural producer of butanol, butyrate, acetone and ethanol. The pattern of metabolites reflects the partitioning of redox equivalents between hydrogen and carbon metabolites. Here the exogenous genes of ferredoxin-NAD(P) oxidoreductase (FdNR) and trans-enoyl-coenzyme reductase (TER) are introduced to three different Clostridium acetobutylicum strains to investigate the distribution of redox equivalents and butanol productivity. The FdNR improves NAD(P)H availability by capturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The co-factor NADH plays an important role in butanol biosynthesis, and insufficient intracellular NADH supply of solventogenic Clostridium limits the production of butanol (Li et al 2015; Qi et al 2018). Therefore, increasing the supply of NADH is of great significance for butanol production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The co-factor NADH plays an important role in butanol biosynthesis, and insufficient intracellular NADH supply of solventogenic Clostridium limits the production of butanol (Li et al 2015; Qi et al 2018). Therefore, increasing the supply of NADH is of great significance for butanol production.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NADH was involved in 43 reactions in Escherichia coli and 65 reactions in Saccharomyces cerevisiae (Nielsen 2003). Therefore, redox balance is of great significance for maintaining normal cell growth and physiological metabolism, and NADH plays an important role in maintaining the redox balance (Qi et al 2018). In addition, NADH also could affect the products formation and metabolic flux redistribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brockarchaeota BDH's are homologues to sequences from obligately anaerobic, thermophilic bacteria that can degrade complex plant saccharides such as xylan (i.e Caldicoprobacter oshimai 24 and Hungateiclostridium thermocellum 25 ) or cellulose (Hungateiclostridium alkalicellulosi). To investigate if Brockarchaeota can oxidize or produce butanol, we searched for genes involved in production of butanol in two model organisms; Clostridium acetobutylicum 26,27 which is one of the few organisms that produces butanol as a fermentation product, and Saccharomyces cerevisiae 28 involved in butanol and isopropanol production. We found that Brockarchaeota genomes lack the key enzymes involved in the fermentation of pyruvate to butanol (butanal dehydrogenase, butyryl-CoA dehydrogenase, enoyl-…”
Section: Utilization Of C1 Compounds and Central Carbon Metabolismmentioning
confidence: 99%
“…55 This is not surprising in light of a recent study that showed Ter is detrimental to ABE fermentation when introduced in C. acetobutylicum. 56 For comparison, the previously best reported butanol production in engineered acetogenic clostridia was ~2 mM. 15 Moreover, the Bcd-EtfA:EtfB complex is a delicate complex that is extremely oxygen sensitive 57 and has so far been inactive in E. coli lysates (in alignment with previous reports that highlighted difficulties expressing Bcd in E. coli), 52 highlighting an area for potential improvement of iPROBE (i.e., compatibility of E. coli lysates with non-model organisms).…”
Section: Figure 5 Cell-free Pathway Testing Combined With Data-drivementioning
confidence: 99%